Closure in Classical Themes: The Role of Melody and Texture in Cadences, Closural Function, and the Separated Cadence - Richards, Mark (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2010)
This article challenges two of William E. Caplin’s basic precepts regarding cadences in the classical style. First, the author argues that melody and texture contribute to the onset of cadential function. Second, he contends that themes may end not only with a half or authentic cadence, but also with a “closural function”, which substitutes for cadential function through a “cadence-like progression”. Moreover, he discusses how a theme may end with a cadence such that its melody and bass resolve at different times, a phenomenon he calls the separated cadence.